Importance of oxygen in single-walled carbon nanotube growth: Insights from QM/MD simulations. (September 2017) - Wang, Ying; Song, Wei; Jiao, Menggai; Wu, Zhijian; Irle, Stephan
Abstract: Quantum chemical molecular dynamics simulations based on the density-functional tight-binding (DFTB) method were performed to investigate the role of oxygen in single-walled carbon nanotube (SWCNT) growth process. We found that a suitable content of oxygen in an iron nano-catalyst particle can reduce the internal thermal mobility of Fe atoms in catalyst due to the formation of strong FeO bonds. These strong FeO bonds also cause reduction of the iron nano-catalyst particle diameter and hence accelerate the collisions of carbon atoms on the catalyst particles. Contrarily, the high electronegativity of oxygen will induce positive charges on the Fe surface and consequently slow down the thermal mobility of adsorbed carbon atoms, causing a reduction of the nucleation rate. By tuning these two opposing factors with the oxygen contents of the iron nanoparticles, potentially highly efficient syntheses of SWCNT including diameter control can be carried out. The current results indicated that in our simulations the optimum ratio of iron and oxygen was 6:1. The observed reduced iron mobility may have implications for Ostwald ripening and for the control of the catalyst shape. Graphical abstract: